Bone quality and quantity measurement techniques in dentistry - Defne Yalçın Yeler (Cumhuriyet University, 2016)
In dentistry, finding a reliable method for measurement mineral density of bone and bonestrength in jaw bones is not only beneficial for implant planning, but also benefical in earlydiagnosis of diseases which effects the mineral density of bone like osteoporosis. Dual-energyX-ray absorptiometry (DXA) method is considered as a gold standard for measurement of bonemineral density in medicine. DXA yields quantitative information on bone structure. In additionDXA, imaging methods which given detailed qualitative information have been developed.Finding a method, which can be also applied on jaw bones and will not damage to the patientand offering a correct information that might be contrubute in dentistry especially with respectto implant and periodontal operations.The aim of the present article, is to provide basic information to reader from past to presentabout main procedures on assessment of bone structure also including jaw bones and theadvantages and disadvantages of these methods.